Improved irradiation resistance of high entropy nanolaminates through interface engineering - Q Xu; J Eckert; D Şopu (Materials Futures)
Bi-phase interfacial engineering is an effective method for improving irradiation resistance, as interfaces play a critical role in defect generation and annihilation. In this work, molecular dynamics simulations are performed to investigate the evolution of the high entropy crystalline/amorphous laminates under ion irradiation. The effects of the crystalline/amorphous interface (ACI) on the distribution of point defects in the high entropy alloy (HEA) as well as on the microstructure evolution in metallic glass (MG) plates are investigated. During irradiation, fewer activated point defects were found in the HEA plate of the MG/HEA laminates compared to a free-standing HEA. In addition, the interface acts as a defect sink, accelerating the annihilation of interstitials at the interface. As a result, residual vacancies accumulate in the crystalline region following the first cascade, leading to a segregated distribution and an imbalance between the vacancies and interstitials in the HEA plate. Vacancy accumulation and clustering are responsible for the formation of stacking faults and complex dislocation networks in the HEA plate in the subsequent overlapping cascades. The interface also acts as a crystallization seed, accelerating the crystallization of the MG plate during irradiation process. However, the structural damage in the MG plate is mitigated by the redistribution of the free volume generated in the collision cascade zone, resulting in structural stability of the MG plate in the overlapping cascades.